2023
DOI: 10.1055/s-0043-1770096
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Anti-Xa Assays: A Multicenter Prospective Study in Critically Ill and Noncritically Ill Patients Receiving Unfractionated Heparin

Abstract: Background The presence of dextran sulfate (DS) in reagents and the type of blood collection tube (citrate/citrated-theophylline-adenosine-dipyridamole [CTAD]) can lead to discrepancies between unfractionated heparin (UFH) anti-Xa levels. Objectives To evaluate the extent of the effect (1) of different reagents containing or not containing DS and (2) of the blood collection tubes, on UFH anti-Xa levels, in various clinical situations (NCT04700670). Methods We prospectively included pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This effect had already been identified for protamine sulfate by Mouton et al. [ 5 ] and more recently in the DEXHEP trial [ 43 ], but the effect of the added concentration of DS had never been studied so far.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This effect had already been identified for protamine sulfate by Mouton et al. [ 5 ] and more recently in the DEXHEP trial [ 43 ], but the effect of the added concentration of DS had never been studied so far.…”
Section: Discussionmentioning
confidence: 87%
“…One limitation of this study is its in vitro design. However, previous studies performed using in vivo samples of patients receiving UFH also identified increased FXa inhibition after the addition of low DS concentration [ 5 , 43 ]. Second, we used commercial NPP produced by plasmapheresis, which could behave differently from PPP obtained by direct blood collection and centrifugation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, some methods in volve dextran sulphate or require an addition of exogenous antithrombin, whereas others do not. In the presence of high concentrations of dextran sulphate, FXa inhibition is much stronger than that predicted from added UFH amounts, 23, 24 which is presumably related to greater availabil ity of UFH for interaction with antithrombin in the assay. As for antithrombin, its inclusion in an antithrombin assay may artificially increase the perceived anti Xa effect, and may not accu rately reflect actual in vivo anticoagulation, es pecially if a patient has reduced antithrombin levels.…”
Section: Review Articlementioning
confidence: 93%
“…18 Regular monitoring of anticoagulant activity is crucial for ensuring successful management and safe administration of anticoagulation therapy. A French multicenter study 19 alerted to the significant overestimation of anti-Xa levels in anti-Xa assays using dextran-containing reagents post heparin neutralization by protamine, warranting caution. Adherence plays a pivotal role in the successful management of anticoagulants, significantly influencing effectiveness and treatment outcomes.…”
Section: Working Against the Clot Anticoagulation Managementmentioning
confidence: 99%